Интегральные двухсторонние кремниевые микростриповые детекторы - Perevertailo, V. L. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The problems of design, technology and manufacturing double-sided silicon microstrip detectors using standard equipment production line in mass production of silicon integrated circuits are considered. The design of prototype high-energy particles detector for experiment ALICE (CERN) is presented. The parameters of fabricated detectors are comparable with those of similar foreign detectors, but they are distinguished by lesser cost.